2022
DOI: 10.2106/jbjs.21.00789
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Exosomes Promote Growth Plate Repair and Reduce Limb-Length Discrepancy in Young Rats

Abstract: Background: The objective of this study was to examine the therapeutic effects of human mesenchymal stromal/stem cell (MSC) exosomes in a rat model of growth plate injury.Methods: A growth plate defect was surgically created on the distal part of the right femur of 40 female Sprague-Dawley rats. A single intra-articular injection of 100 mg of MSC exosomes in 100 mL of phosphate-buffered saline solution (PBS), or an equivalent volume of PBS alone, was administered to the right knee immediately after surgery. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Even though bone bridge formation after a sustained GP injury has long been assumed to be the main reason for bone length discrepancies, recent studies have demonstrated that the formation of a bone bridge may only play a minor role and might only develop when certain areas of the GP are affected [ 33 , 34 , 35 ]. For instance, Wong et al [ 36 ] showed reduced limb length discrepancy despite bone bridge formation when they treated a growth plate injury with mesenchymal stem cell (MSC) exosomes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though bone bridge formation after a sustained GP injury has long been assumed to be the main reason for bone length discrepancies, recent studies have demonstrated that the formation of a bone bridge may only play a minor role and might only develop when certain areas of the GP are affected [ 33 , 34 , 35 ]. For instance, Wong et al [ 36 ] showed reduced limb length discrepancy despite bone bridge formation when they treated a growth plate injury with mesenchymal stem cell (MSC) exosomes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al studied the effect of human mesenchymal stem exosomes on damaged growth plates in female Sprague-Dawley rats 58 . Their findings revealed significant improvements in the repair of the damaged physes and a reduction in the magnitude of limb-length discrepancy in the experimental group.…”
Section: Basic Sciencementioning
confidence: 99%
“…Therefore, as a minimally invasive cell-free therapy, MSCs-derived Exos can promote the growth plate cartilage regeneration and reduce limb discrepancy after injury. 98 Another study found that after treatment with BMSCs-derived EVs, the proliferating zone at the growth plate injury site showed flat and self-oriented chondrocytes began to arrange into columnar shapes parallel to the bone growth axis, which is similar to the arragenment of the growth plate cartilage structure. The results showed that BMSCs-EVs have differentiation potential and promoted the formation of correct spatial structure in different growth plate regions, especially in proliferative zone.…”
Section: Introductionmentioning
confidence: 98%